Accuracy of transverse cerebellar diameter by ultrasonography in the evaluation gestational age of fetus - Prasad, V Natraj; Dhakal, Vivek; Chhetri, Pramod Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Estimation of the length of gestation is of paramount importance to obstetricians. The fetal cerebellum grows progressively along gestational period and transverse cerebellar diameter can be used as a new biometric parameter to assess the gestational age of fetus. This study was done to evaluate the accuracy transverse cerebellar diameter against other regularly measured parameters like biparietal diameter, head circumference, abdominal circumference and femur length in pregnant women between 15 to 40 weeks of gestation. Materials & Methods: In this study of 60 pregnant women between 15-40 weeks of gestation, all the parameters like biparietal diameter, head circumference, abdominal circumference, femur length and transverse cerebellar diameter were measured with ultrasonography. The measured values were then correlated with gestational age using regression coefficient. Results: Gestational age estimated by transverse cerebellar diameter (R2 = 0.989; p < 0.001) had good predictive value which was comparable to gestational age estimated by biparietal diameter (R2 =0.929; P < 0.01), head circumference (R2 =0.964; P < 0.01), abdominal circumference (R2 =0.931; P < 0.01) and fetal length (R2 = 0.966; P < 0.01). Conclusion: Transverse cerebellar diameter has a good predictive accuracy for gestational age estimation which is comparableto other routinely used parameters and can be used as an alternative parameter to predict the gestational age.